A compact low frequency dual band liquid crystal polymer antenna for VHF and UHF band applications. (2021) - Srilekha, Gandu; Pardhasaradhi, P.; Madhav, B.T.P.; VenkateswaraRao, M.; Rao, M.C.
Abstract: This article presents a compact low frequency dual band Liquid crystal polymer (LCP) antenna for Very High Frequency (VHF) and Ultra High Frequency (UHF) band applications. The proposed antenna is having dimensions of 19 × 19 × 0.1 mm 3, which is compact in size and designed on FR4, Rogers/ RT Duroid, Polyimide and LCP substrate materials with CPW (Coplanar Waveguide) feed having CSRR (Complementary Split Ring Resonator) structure placed on ground plane. Simulation results of the designed antennas are compared with each other and finally LCP substrate material exhibits better properties compared with all other substrate materials. The designed antenna on LCP operates in frequency ranges of VHF and UHF (0.085–0.29 GHz and 0.805–2.58 GHz) respectively. The designed antenna on LCP is resonating at 0.14 GHz and 1.425 GHz frequencies with reflection coefficient of −24.29 dB and –33.39 dB respectively. The designed antenna on LCP has the gain of 12. 82 dB at 0.14 GHz and 6.27 dB at 1.425 GHz respectively. The designed antenna on LCP is fabricated and analyzed by using combinational analyzer. Measured results of proposed antenna on LCP are in good agreement with simulated results.